Composition and method for protective layer for metal electrode of secondary battery

By using a combination of organic binder and pyrolyzed magnesium oxide particles on the lithium electrode as the protective layer material, the problem of chemical instability during the circulation of lithium metal batteries is solved, and higher cycle stability and electrochemical cycle capabilities are achieved.

CN119627260APending Publication Date: 2025-03-14EVONIK OPERATIONS GMBH
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411240073.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-06
Filing Date
2024-09-05
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing lithium metal batteries have chemical instability during circulation, resulting in limited cycle life and it is difficult to obtain stable coating dispersions and coating slurries on the metal negative electrode.

Method used

Using an organic binder and surface-modified magnesium oxide particles generated by pyrolysis, as the protective layer material for the lithium electrode, the magnesium oxide particles obtained by pyrolysis have a high specific surface area and hydrophobicity, which improves the chemical stability of the electrode.

Benefits of technology

The cycle stability of lithium metal batteries is significantly improved, and stable coating dispersion and coating slurry are obtained on the metal negative electrode, which extends the electrochemical cycle capability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627260A_ABST
    Figure CN119627260A_ABST
Patent Text Reader

Abstract

A composition for a coating of an electrode of a secondary battery, in particular a lithium battery, comprising an organic binder and a metal compound selected from the group consisting of surface-modified magnesium oxide, surface-modified lithium-doped magnesium oxide, surface-modified magnesium phosphate or mixtures thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention generally relates to a composition and method for a protective layer for an electrode of a secondary battery, especially a lithium battery. The present invention further relates to an electrode and a secondary battery, especially a lithium battery using an electrode with a protective layer. The method further relates to an electronic or electrical device using a secondary battery, especially a lithium battery. Background Art

[0002] Lithium metal batteries (LMBs), such as lithium-sulfur (Li-S), lithium-air (Li-air), and solid-state lithium batteries, have been reported to overcome at least some of the limitations of lithium-ion batteries, such as the lack of high energy storage capacity. However, the inherent properties of metallic Li create issues regarding battery safety and instability, and can lead to limited cycle life. The high reactivity of Li triggers different processes that generally have an adverse effect on the cycle life of the battery, such as liquid electrolyte degradation, solid-electrolyte-interface (SEI) formation, corrosion of the Li negative electrode due to the presence of trace water in the electrolyte, Li dendrite formation, and lithium passivation by polysulfide shuttle effect in Li-S cells. Therefore, successful stabilization / protection of the Li negative electrode is highly desirable for further development of LMB technology.

[0003] Recent approaches to stabilize the lithium metal-electrolyte interface with soft polymer coatings show potential for improving the rate and capacity of lithium metal cycling. Thus, controlled protection of the Li anode with organic and / or inorganic materials has been revealed to have a beneficial effect on battery performance.

[0004] CN109473627A describes the preparation of a composite electrode comprising lithium metal, inorganic nanomaterials with a particle size of 50 to 500 nm (such as titanium oxide, aluminum oxide, silicon dioxide, boehmite, zirconium oxide), an organic polymer and a membrane material by the following steps: (1) preparing a solution of polymer and inorganic particles; (2) coating the solution on the membrane surface and then drying it; (3) grinding the dried composite material prepared in step (2) with metallic lithium to form composite electrode particles covered with a composite layer; and (4) shaping the composite electrode material to form a metallic lithium electrode sheet containing lithium particles covered with a protective layer.

[0005] US20170062829 A1 describes a lithium metal battery comprising a lithium metal negative electrode having a protective layer comprising a polymer (e.g., styrene-isoprene copolymer), at least one metal salt, and a nitrogen-containing additive such as Li 3 N. The protective layer may also contain inorganic particles such as TiO 2 、ZnO、Al2 O 3 、SiO 2 .

[0006] US20140220439 A1 describes an alkali metal anode coated with a protective coating comprising inorganic particles, such as those containing the elements Al, Mg, Fe, Sn, Si, B, Cd, Sb, dispersed throughout a matrix of an organic compound, such as a pyrrolidine derivative.

[0007] US20170301920 A1 describes a lithium metal electrode coated with a protective layer comprising a polymer ionic liquid, optionally inorganic nanoparticles such as SiO 2 、Al 2 O 3 、TiO 2 、MgO、ZrO 2 , ZnO, Fe 3 O 4 , barium titanate, lead titanate, lithium nitride, lithium aluminate.

[0008] Jang et al. described the preparation of a coated lithium metal anode in Adv. Funct. Mater. 2019, vol. 29 (48), No. 1905078, which includes a ZrO with a particle size of 5 μm. 2 Powder or Al with an average particle size of 500nm 2 O 3 The powder was mixed with polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP) polymer, DMF and electrolyte, and the slurry was coated on a 450 μm thick lithium metal foil and dried to form a 21.7 μm thick coating.

[0009] US20180316051A1 describes a negative electrode for a lithium metal battery, comprising a lithium metal layer, a lithium metal alloy, and a protective layer having inorganic particles having a particle size greater than about 1 μm to about 100 μm or less.

[0010] WO 2019149939 A1 describes a lithium metal anode coated with a protective layer having a thickness of 0.01 to 10 μm, the protective layer consisting of a polymer and up to 30% by weight of inorganic particles (such as Al 2 O 3 、MnO、MnO 2 、SiO 2 、TiO 2 、ZnO、ZrO 2 , Fe 2 O 3 , CuO, silicate, aluminosilicate, borosilicate).

[0011] Lee, Y., Fujiki, S., Jung, C, et al. describe a high-performance all-solid-state lithium metal battery with a sulfide electrolyte and an Ag-C composite negative electrode without excess lithium in Nature Energy volume 5, pages 299–308 (2020). The metal layer of the composite Ag-C negative electrode of the system can effectively regulate Li deposition, which leads to extended electrochemical cycling capability. Therefore, in this case, instead of using a typical lithium negative electrode, a silver-based negative electrode is used, on which a lithium layer is reversibly deposited during the operation of the lithium battery.

[0012] US20200106103A1 describes a material comprising a protective layer of a polymer or a mixture of a polymer and an inorganic material, wherein the inorganic material is selected from HfO 2 、SrTiO 3 SnO 2 、CeO 2 , MgO, NiO, CaO, BaO, ZnO, ZrO 2 、Al 2 O 3 、TiO 2 、SiO 2 , Li 3 PO 4 , Li 2 O, LiF, LiOH, Li 2 CO 3 , Li-containing metal oxides, Li-containing phosphates, and any combination thereof.

[0013] WO2021144299 A1 describes a lithium metal negative electrode coated with a protective layer, the protective layer having a thickness of 0.5 to 500 μm, comprising a polymer and a metal compound, the metal compound being selected from aluminum oxide, silicon dioxide, zirconium oxide, a mixed oxide containing zirconium, a mixed oxide containing aluminum, lithium zirconium phosphate and a mixture thereof, wherein the metal compound is composed of aggregates of primary particles having a number average primary particle size d50 of 5 nm–100 nm obtained by pyrolysis.

[0014] Problems and Solutions

[0015] WO2021144299 A1 teaches that the higher BET surface area of ​​nano-sized metal oxide particles further improves the electrochemical performance of Li metal batteries. However, increasing the BET surface area of ​​the metal oxide particles in the protective layer makes it difficult to obtain a stable coating dispersion and coating slurry on the metal negative electrode.

[0016] Importantly, the physicochemical properties of inorganic particles, such as the type of particles, their particle size, particle size distribution, aggregation and agglomeration, the surface of the particles, and the content of such particles in a protective coating or layer for a metallic lithium electrode, affect the chemical stability of the metallic lithium electrode during cycling of a lithium metal battery.

[0017] The problem addressed by the present invention is how to provide higher cycle stability for secondary batteries such as lithium batteries, and especially lithium metal batteries.

[0018] The present invention provides an improved composition for a protective layer of a metal electrode of a secondary battery, which improves the cycle stability of the secondary battery, particularly a lithium battery, and more particularly a lithium metal battery. Summary of the invention

[0019] The present invention generally relates to a composition and method for a protective layer of a metal electrode for a secondary battery, to the metal electrode (the secondary battery uses the electrode), and to an electronic or electrical device using the secondary electrode, as defined in the independent claim. Embodiments of the invention are defined in the dependent claims. Features from one embodiment may be combined with one or more features of another embodiment, as long as the features do not contradict each other.

[0020] In the course of comprehensive experiments, it was surprisingly found that the combination of an organic binder with pyrolytically produced, surface-modified magnesium oxide particles is particularly suitable for coating metal electrodes, such as lithium electrodes for lithium-ion batteries.

[0021] These and other features and advantages of the present invention will become apparent from the following description and accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a simplified schematic diagram of an electrode according to one embodiment of the present invention.

[0023] Figure 2 is a flow chart of a method for manufacturing an electrode according to one embodiment of the present invention.

[0024] Figure 3 is a simplified schematic diagram of a secondary battery according to one embodiment of the present invention.

[0025] Figure 4 is a simplified schematic diagram of an electronic or electrical device according to one embodiment of the present invention.

[0026] Figure 5 Shown at 1mA / cm 2 At a current density of Cycling of polarization voltage using Alu 130 (Comparative Example 1) as filler in the protective layer on the Li layer.

[0027] Figure 6 Shown at 1mA / cm 2 Cycling of polarization voltage using Alu 130 805 (Example 6) as a filler in the protective layer on the Li layer at a current density of .

[0028] Figure 7 Shown at 1mA / cm 2 Cycling of polarization voltage using Alu 200 (Example 7) as a filler in the protective layer on the Li layer at a current density of .

[0029] Figure 8 Shown at 1mA / cm 2 Cycling of polarization voltage using MgO-01 (Example 8) as the filler in the protective layer on the Li layer at a current density of .

[0030] Fig. 9 Shown at 1mA / cm 2 Cycling of polarization voltage using MgO 805 (Example 10) as a filler in the protective layer on the Li layer at a current density of .

[0031] Fig.10 It shows that without a protective layer, the 2 Cycling using polarization voltage at a current density of (Comparative Example 2).

[0032] Fig.11 Shown are examples at 1 mA / cm 2 Polarization voltage at the 200th cycle at a current density of . DETAILED DESCRIPTION

[0033] Reference Figure 1 According to one embodiment of the present invention, there is provided an electrode 11 for a secondary battery. The electrode 11 includes a metal layer 10 coated with a coating layer 14. The coating layer 14 includes an organic binder "OB" and a metal compound "MC".

[0034] The metal compound MC is selected from the group consisting of hydrophobic surface-modified fumed magnesium oxide, hydrophobic surface-modified lithium-doped fumed magnesium oxide, hydrophobic surface-modified fumed magnesium phosphate and mixtures thereof.

[0035] The metal compound MC is obtained by a pyrolysis (also called "fume" or "fumed") process. In the context of the present invention, the pyrolysis process may involve flame oxidation, flame hydrolysis or flame pyrolysis. This process involves the oxidation or hydrolysis of a hydrolyzable or oxidizable starting material, usually in a hydrogen and / or oxygen flame.

[0036] Preferably, the pyrolysis may be flame spray pyrolysis. An example of flame spray pyrolysis is described in WO 2015173114 A1 entitled "Method for producing mixed oxide powder comprising lithium, lanthanum, and zirconium" by Katusic et al., and in US 2022 / 0306485 A1 entitled "Preparation of nanostructured mixed lithium zirconium oxides by means of spray pyrolysis" by Shafer et al., and elsewhere.

[0037] The flame spray pyrolysis preferably comprises the following steps:

[0038] atomizing at least one solution of a metal precursor by means of an atomizer gas to provide an aerosol,

[0039] in a reaction space of a reactor, reacting the aerosol with a flame obtained by igniting a mixture of a fuel gas and an oxygen-containing gas to obtain a reactant stream,

[0040] cooling the reaction stream, and

[0041] The solid metal oxide is subsequently removed from the reactant stream.

[0042] Therefore, flame spray pyrolysis (FSP) can include atomizing a solution of a metal precursor (such as magnesium chloride, magnesium sulfate, magnesium carbonate, magnesium hydroxide, magnesium lactate, magnesium citrate, magnesium glutamate and magnesium aspartate) in an atomizer (also referred to as an evaporator), and sending steam into a mixing chamber. Steam can be transferred to the mixing chamber via an inert carrier gas. Separately, a fuel gas comprising hydrogen and primary air can be introduced into the mixing chamber. Air can be optionally enriched with oxygen. Air can be optionally preheated before being supplied to the mixing chamber. Compared with the theoretical amount required for the formation reaction, hydrogen can be preferably used in a small amount in excess.

[0043] The magnesium oxide powder formed by the FSP can then be separated from the gas in a downstream gas-solid separation unit and deposited at the bottom of the gas-solid separation unit (e.g., a cyclone separator) and collected via the bottom outlet. The powder can be transferred to a deacidification device for removing the acid from the powder, and the magnesium oxide powder is treated with air and steam, which are fed in a countercurrent direction within the device at an elevated temperature of 100°C-700°C, more preferably 150°C-650°C, even more preferably 200°C-600°C, still more preferably 250°C-550°C. The powder is collected in a silo and can be further processed as desired, for example, it can be packaged.

[0044] Suitable starting materials for the pyrolysis process may include organic and / or inorganic magnesium compounds, such as magnesium chloride, magnesium nitrate, magnesium acetate and magnesium carboxylates. For example, in the flame hydrolysis process, a metal precursor such as magnesium chloride is typically vaporized and reacted in a flame generated by the reaction of hydrogen and oxygen to form magnesium oxide particles. The powder thus obtained is referred to as a "pyrolysis" or "gas phase" magnesium oxide metal compound.

[0045] The reaction initially forms highly dispersed primary particles, which in the further course of the reaction coalesce to form aggregates, i.e. firmly bound primary particles and agglomerates. Agglomerates are relatively weakly bound aggregates. The aggregate size of these powders is usually in the range of 0.05 μm-50 μm.

[0046] These powders are converted into particles in the nanometer (nm) range suitable for the purposes of the present invention by appropriate grinding which destroys the agglomerates but does not substantially modify the aggregation of the primary particles.

[0047] The metal compound (eg magnesium oxide) used in the present invention may preferably have 1 m 2 / g to 500m 2 , more preferably 20m 2 / g to 400m 2 / g, even more preferably 40m 2 / g to 350m 2 / g, most preferably 50m 2 / g to 300m 2 / g specific surface area (BET).

[0048] The specific surface area, also referred to as BET surface area for short, can be determined in accordance with DIN 9277:2014 by nitrogen adsorption according to the Brunauer-Emmett-Teller method.

[0049] In some embodiments, the product of the pyrolysis process is further heat treated at a temperature of 100 to 350°C.

[0050] In some embodiments, a mixed metal oxide containing magnesium oxide can be used. For example, the mixed oxide can include magnesium oxide, lithium-doped magnesium oxide, magnesium phosphate, or a mixed oxide or phosphate containing lithium, magnesium, phosphorus, and oxygen. These compounds are referred to as metal compounds MC.

[0051] The particles of the metal compound used in the present invention obtained by pyrolysis are usually mostly in the form of aggregates, although some particles may be in the form of non-aggregated primary particles. The metal compound MC preferably has a number average aggregate particle size d50 of less than 2 μm, preferably 20 nm-1 μm, more preferably 30 nm-800 nm, even more preferably 40 nm-600 nm, most preferably 50 nm-500 nm. The number average particle size d50 can be measured in a suitable dispersion, for example in an aqueous dispersion, by a static light scattering (SLS) method.

[0052] In some embodiments, agglomerates and partial aggregates can be broken, for example, by grinding or ultrasonic treatment of the powder obtained by the pyrolysis process, which results in particles with smaller particle sizes and narrower particle size distributions. In such embodiments, preferably, the number average aggregate particle size d50 of the metal compound after grinding is 50nm-1000nm, more preferably 100nm-700nm, even more preferably 150nm-500nm, as determined by dynamic light scattering (DLS) or static light scattering (SLS) after ultrasonic treatment of a mixture consisting of 5 wt% of the particles and 95 wt% of a 0.5 g / L sodium pyrophosphate aqueous solution for 300 seconds at 25°C.

[0053] Furthermore, the powder obtained by grinding or ultrasonic treatment of the powder obtained by pyrolysis has a span defined as (d90-d10) / d50 of preferably 0.4-1.2, more preferably 0.5-1.1, even more preferably 0.6-1.0, as determined by static light scattering (SLS) at 25°C after ultrasonic treatment of a mixture consisting of 5 wt. % of the particles and 95 wt. % of a 0.5 g / L aqueous sodium pyrophosphate solution for 300 seconds.

[0054] Therefore, the metal compound MC present in the coating 14 of the electrode 11 of the present invention is preferably characterized by a relatively small number average aggregate particle size d50 and a narrow particle size distribution (d90-d10) / d50. This helps to achieve a high quality metal compound coating for the lithium electrode.

[0055] The d values ​​d10, d50, and d90 are often used to characterize the cumulative particle size distribution of a given sample. For example, the d10 diameter is the diameter at which 10% of the sample volume consists of particles smaller than d10, and the d50 is the diameter at which 50% of the sample volume consists of particles smaller than d50. The d50 is also called the "volume median diameter" because it divides the sample equally by volume; the d90 is the diameter at which 90% of the sample volume consists of particles smaller than d90.

[0056] The metal compound present in the electrode of the present invention may have a tamped density of 20 g / L to 1000 g / L. The metal compound that has not been heat treated preferably has a tamped density of 20 g / L-200 g / L, more preferably 25 g / L-150 g / L, even more preferably 28 g / L-130 g / L, still more preferably 30 g / L-120 g / L.

[0057] The tamped density of powdered or coarse granular materials can be determined according to DIN ISO 787-11:1995 "General methods of test for pigments and extenders--Part 11: Determination of tamped volume and apparent density after tamping". This involves measuring the apparent density of the bed after stirring and tamping.

[0058] Surface treated metal compounds

[0059] The metal compound MC present in the coating 14 of the electrode 11 according to the invention is subjected to a surface treatment, in particular a hydrophobic surface treatment, in order to improve the compatibility of the metal compound particles with the organic binder OB and the solvent used during the coating process.

[0060] Therefore, the metal compound MC present in the coating 14 of the electrode 11 is hydrophobic and can have a methanol wettability of greater than 5% by volume, preferably 10% to 80% by volume, more preferably 15% to 70% by volume, even more preferably 20% to 65% by volume, and most preferably 25% to 60% by volume in a methanol / water mixture.

[0061] The term "hydrophobic" or "hydrophobized" in the context of the present invention relates to particles that have a low affinity for polar media such as water. In contrast, hydrophilic particles have a high affinity for polar media such as water.

[0062] The hydrophobicity of hydrophobic materials can be realized by applying appropriate non-polar groups to the particle surface. The hydrophobicity degree of the metal compound can be determined by parameters including its methanol wettability as described in detail in, for example, WO2011 / 076518A1, pages 5 to 6. In pure water, the hydrophobic particles of the metal compound are completely separated from water and float on its surface without being wetted by the solvent. In contrast, in pure methanol, the hydrophobic particles are distributed in the entire solvent volume and completely wetted. In the mensuration of methanol wettability, the maximum methanol content when the metal compound is still not wetted in the methanol / water test mixture is determined, which means that 100% of the metal compound used is kept separated from the test mixture after contacting the test mixture, in a non-wetting form. The methanol content (in % by volume) in the methanol / water mixture is referred to as methanol wettability. The higher this methanol wettability level is, the more hydrophobic the metal compound is. The lower the methanol wettability is, the lower the hydrophobicity of the metal compound is, and the higher the hydrophilicity is.

[0063] Specifically, to determine methanol wettability, in each case 0.2 g (± 0.005 g) of the surface treated particles were weighed into a transparent centrifuge tube. Portions of 8.0 ml of a methanol / water mixture with 10, 20, 30, 40, 50, 60, 70 or 80% methanol by volume were added to each sample. The tubes were shaken for 30 seconds and then centrifuged at 2500 revolutions per minute for 5 minutes. Methanol wettability is defined as the percentage by volume of methanol for a deposit volume of 100%. The higher the number, the higher the hydrophobicity.

[0064] The metal compound of the present invention is preferably surface-treated with a surface treating agent selected from the group consisting of organosilanes, silazanes, acyclic polysiloxanes, cyclic polysiloxanes, and mixtures thereof, thereby being hydrophobized.

[0065] The hydrophobic metal compound preferably has a carbon content of 0.1 wt % to 15.0 wt %, more preferably 0.5 wt % to 12.0 wt %, even more preferably 1.0 wt % to 10.0 wt % and most preferably 1.5 wt % to 8.0 wt %. The carbon content can be determined by elemental analysis according to EN ISO 3262-20:2000-Chapter 8. The analysis sample is weighed into a ceramic crucible, provided with a combustion additive and heated in an induction furnace under an oxygen flow. The carbon present is oxidized to CO 2 .CO 2 The amount of gas is quantified by an infrared detector.

[0066] Metal layer

[0067] The term "layer" in the context of the present invention means a continuous deposition of a respective substance or component on the surface of another substance or component.

[0068] The metal layer 10 of the electrode 11 of the present invention, such as a lithium layer, can be additionally loaded on a metal foil 8 used as a current collector. The metal foil 8 may contain lithium, sodium, potassium, magnesium, calcium, zinc, aluminum, copper, silver, gold, nickel, iron, indium, gallium, steel, stainless steel, titanium or a metal alloy thereof. Such a metal alloy may also contain non-metallic components, such as silicon, germanium. Most preferably, the metal foil 8 may be composed of copper or aluminum, especially if the electrode of the present invention is used in combination with a liquid electrolyte. Stainless steel foil is preferably used in electrodes used in combination with solid electrolytes (such as sulfide electrolytes). The metal foil 8 may have a thickness of 0.5 μm–500 μm, more preferably 1 μm–100 μm, even more preferably 2 μm–50 μm and most preferably 5 μm–30 μm. In some embodiments, the metal foil 8 may be further loaded on a polymer substrate (not shown).

[0069] According to one embodiment of the present invention, the metal layer 10 of the electrode 11 may have a thickness of preferably 2 μm - 500 μm, more preferably 3 μm - 300 μm, even more preferably 5 μm - 200 μm, most preferably 7 μm - 180 μm.

[0070] The metal layer 10 may be disposed on the metal foil 8 by any suitable method, such as vacuum deposition, rolling, electrochemical deposition or lamination, to name a few such methods. These methods are well known in the industry and will not be described in detail.

[0071] coating

[0072] The coating 14 of the electrode 11 comprises an organic binder OB and a metal compound MC selected from hydrophobic surface-modified fumed magnesium oxide, hydrophobic surface-modified lithium-doped fumed magnesium oxide, hydrophobic surface-modified fumed magnesium phosphate or a mixture thereof.

[0073] The weight ratio of metal compound MC to organic binder OB in coating 14 is 0.1 to 10, preferably 0.2 to 9.5, more preferably 0.3 to 9.0, even more preferably 0.4 to 8.5, even more preferably 0.5 to 8.0, even more preferably 0.8 to 7.0 and most preferably 1.0 to 6.0.

[0074] electrode

[0075] The electrode 11 according to an embodiment of the present invention may include a lithium salt, which may be optionally added to the coating layer 14. For example, in some embodiments, the lithium salt may be mixed with the organic binder OB and the metal compound MC, and then the mixture may be applied to the metal layer 10 of the electrode 11.

[0076] The lithium salt may be selected from lithium hexafluorophosphate (LiPF 6), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO 4 ), lithium tetrafluoroborate (LiBF 4 )、Li 2 SiF 6 , lithium trifluoromethanesulfonate, lithium bis(perfluoroethylsulfonyl)imide (LiN(SO 2 CF 2 CF 3 ) 2 ), lithium nitrate, lithium bis(oxalato)borate, cyclo-difluoromethane-1,1-bis(sulfonyl)imide lithium, cyclo-hexafluoropropane-1,1-bis(sulfonyl)imide lithium, and mixtures thereof.

[0077] In a battery using a solid electrolyte, lithium bis(fluorosulfonyl)imide (LiFSI) or lithium bis(2-(trifluoromethylsulfonyl)imide (LiTFSI) may be preferably used as the lithium salt in the coating layer 14 .

[0078] According to one embodiment, the thickness of the coating may be 0.1 μm - 300 μm, more preferably 0.5 μm - 100 μm, even more preferably 1 μm - 50 μm, most preferably 2 μm - 20 μm.

[0079] Organic binder

[0080] The organic binder OB of the coating layer 14 for the electrolyte provides effective adhesion between the particles of the metal compound MC in the coating layer 14 and the surface of the metal layer 10 (eg, lithium layer 10 ).

[0081] The organic binder is selected from the group consisting of poly(vinylidene fluoride), copolymers of vinylidene fluoride and hexafluoropropylene, poly(vinyl acetate), poly(ethylene oxide), poly(methyl methacrylate), poly(ethyl acrylate), poly(vinyl chloride), poly(urethane), poly(acrylonitrile), poly(ethylene glycol), polypropylene glycol, poly(ethylene glycol-co-propylene glycol-co-ethylene glycol), poly(propylene glycol-co-ethylene glycol-co-propylene glycol), polysiloxanes, poly(oxyethylene) methacrylate, poly(ethylene glycol) diacrylate, poly(propylene glycol) diacrylate, poly(ethylene glycol) dimethacrylate, poly(propylene glycol) dimethacrylate, poly(ethylene glycol)-dimethyl ether, poly(ether amines), copolymers of ethylene and vinyl acetate, carboxymethyl cellulose, poly(imides), and mixtures thereof.

[0082] More preferably, the organic binder may be one of PVDF or PVDF-HFP. In particular, PVDF-HFP is more preferably used for coating on lithium (Li) metal layers, while PVDF is more preferably used for other metal layers, such as copper (Cu) layers / foils.

[0083] Method for manufacturing an electrode

[0084] Reference now Figure 2 According to an embodiment of the present invention, there is provided a method for manufacturing the electrode 11 of the present invention, the method comprising:

[0085] In step 102, a mixture including an organic binder OB as described above and a metal compound MC as described above obtained by a pyrolysis method is prepared; in step 104, the mixture prepared in step 102 is applied on the surface of the metal layer 10 to form a pre-coating layer; and in step 106, the pre-coating layer prepared in step 104 is dried and / or cured to form a coating layer 14. In one embodiment, in step 102 of preparing the mixture of the organic binder OB and the metal compound MC, a lithium salt may also be added and mixed with the organic binder OB and the metal compound MC. In one embodiment using a semi-solid or solid electrolyte, since no liquid enters the protective layer, the Li ion conductivity in the protective layer may be increased by adding the lithium salt together with the organic binder and the metal compound MC.

[0086] The metal compound MC is selected from hydrophobic surface-modified fumed magnesium oxide, hydrophobic surface-modified fumed lithium-doped magnesium oxide, hydrophobic surface-modified fumed magnesium phosphate and mixtures thereof. The lithium salt may be selected from lithium hexafluorophosphate (LiPF 6 ), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO 4 ), lithium tetrafluoroborate (LiBF 4 )、Li 2 SiF 6 , lithium trifluoromethanesulfonate, lithium bis(perfluoroethylsulfonyl)imide (LiN(SO 2 CF 2 CF 3 ) 2 ), lithium nitrate, lithium bis(oxalato)borate, cyclo-difluoromethane-1,1-bis(sulfonyl)imide lithium, cyclo-hexafluoropropane-1,1-bis(sulfonyl)imide lithium, and mixtures thereof.

[0087] The metal compound is composed of a powder obtained by pyrolysis as described above. Preferably, the powder obtained by pyrolysis can also be subjected to grinding or ultrasonic treatment and surface modification treatment to further reduce the particle size of the powder and make them hydrophobic. The weight ratio of the metal compound to the organic binder is 0.1 to 10, preferably 0.2 to 9.5, more preferably 0.3 to 9.0, more preferably 0.4 to 8.5, more preferably 0.5 to 8.0, more preferably 0.8 to 7.5, more preferably 1.0 to 6.0.

[0088] A solvent may be optionally used in step 102 of the method of the present invention and may not be particularly limited as long as it can dissolve the organic binder OB and does not react with the metal compound (e.g., lithium metal) during the coating process. A non-exhaustive list of suitable solvents may include 1,2-dimethoxyethane, diethyl ether, tetrahydrofuran, dimethoxyethane, dimethoxyethane, dimethoxycarbonyl ... alkane, bis(2-methoxyethyl) ether, pentane, hexane, heptane, octane, decane, toluene, ethanol, isopropanol, N-methyl-2-pyrrolidone, triethyl phosphate, dimethyl sulfoxide, methyl ethyl ketone, methyl isobutyl ketone, benzaldehyde, N,N-dimethylformamide, dimethylacetamide, acetonitrile, cyclohexanone, ethyl acetate, propylene carbonate, ethylene carbonate, diethylene glycol monomethyl ether, triethylene glycol methyl ether, acetylacetone, acetone and mixtures thereof.

[0089] The mixture prepared in step 102 of the method according to the present invention can be obtained from two or more mixtures, for example, the first mixture can contain metal compound particles and a first solvent, and the second mixture can contain an organic binder, a second solvent and an optional lithium salt. The first solvent and the second solvent can be the same or different. The first solvent and the second solvent can preferably be the same.

[0090] Preferably, the first mixture may contain 1%-70% by weight, more preferably 3%-60%, even more preferably 5%-50%, and most preferably 7%-45% of the metal compound and 30%-99% by weight, more preferably 40%-97%, even more preferably 50%-95%, and most preferably 55%-93% of the solvent. The second mixture may contain 0.1%-90% by weight, preferably 0.5%-50%, more preferably 1%-20%, more preferably 2%-10% of the organic binder and 10%-99.9% by weight, preferably 50%-99.5%, more preferably 80%-99%, more preferably 90%-98% of the solvent.

[0091] In step 104 of the method of the present invention, the metal layer 14 is coated with the mixture prepared in step 102 to form a pre-coating layer including a metal compound and an organic binder on the surface of the metal layer 14 .

[0092] Any suitable coating method which allows the application of relatively thin coatings may be applied.An example of a suitable apparatus for the coating step is the doctor blade apparatus SA-202 commercially available from the manufacturer Tester Sangyo.

[0093] In step 106 of the method of the present invention, the pre-coating layer on the metal layer 14 in step 104 is further dried and / or cured on the surface of the metal layer 14 , resulting in the formation of a coated metal layer 14 on the metal layer 10 of the electrode 11 .

[0094] The curing of the mixture of the pre-coat layer can occur, for example, by polymerization, a cross-linking reaction or another type of chemical reaction or by physical curing (e.g., by evaporation of solvents, or other volatile components of the adhesive). Chemical curing can occur, for example, thermally or under the action of UV radiation or other radiation.

[0095] Depending on the system used, step 106 may be preferably performed at a temperature of 0°C to 500°C, more preferably 5°C to 400°C, more preferably 10°C to 300°C, more preferably 20°C to 150°C. Drying / curing step 106 may be performed in the presence of air, or preferably with the exclusion of oxygen, such as under a protective gas atmosphere of nitrogen or argon. Drying / curing step 106 may be performed at standard pressure. Drying and curing step 106 may be performed under reduced pressure, such as under vacuum.

[0096] The purpose of the electrode

[0097] The present invention further relates to the use of the electrode 11 according to the invention as a component of a lithium metal, lithium ion battery or other secondary battery, preferably a lithium metal battery or a lithium ion battery, more preferably a lithium metal battery.

[0098] Figure 3 A lithium metal battery, generally indicated by the numeral 40, is shown, which includes separators 16, 18, a first electrode 11 and a second electrode 20, 22. The first electrode 11 corresponds to Figure 1 The electrode 11 of the present invention having a coating 14, a metal layer 10 and a foil 8. The coating 14 may include an organic binder OB and a metal compound MC as described above, and in some embodiments, a lithium salt. The coating 14 may preferably be in the form of a powder of nanoparticles. The coating 14 may be formed on Figure 1 The coating 14 may have a thickness of 0.1 μm-300 μm, more preferably 0.5 μm-100 μm, even more preferably 1 μm-50 μm and most preferably 2 μm-20 μm. The electrolyte 24 is placed around the separators 16, 18 and between the first electrode and the second electrode. For example, the separators 16, 18 may include a polymer film 16 covered with a ceramic coating 18 on both sides thereof. Figure 4 As schematically shown in FIG. 4 , lithium metal batteries 40 can be used in electronic and electrical devices 400, including, for example, mobile phones, computers (laptops, desktops, tablets), electronic watches, key fabs, appliances, power tools, vacuum cleaners, electric lawn mowers, and electric vehicles, to mention only a few of the many uses for lithium batteries. The second electrode 20, 22 can include an active material 20 on the electrode plate 20.

[0099] In some embodiments, the method may include operatively connecting the first electrode 11 in the secondary battery 40 as a negative electrode of the secondary battery 40. The secondary battery 40 may be disposed within an electronic or electrical device 400 for providing power to the device 400.

[0100] Example

[0101] Metal compound samples:

[0102] Alu 130, which is a commercially available product of Evonik Operations GmbH.

[0103] Alu 130 805, which has a BET surface area of ​​130 m 2 Use of / g OCTMO (octyltrimethoxysilane) surface-modified fumed alumina particles.

[0104] Alu 200, which is prepared by gas phase synthesis, has a BET surface area of ​​200 m 2 / g of fumed alumina particles.

[0105] MgO-1, which is produced by flame spray pyrolysis, has a BET of 70 m 2 / g of fumed magnesium oxide particles.

[0106] MgO-8, which is produced by flame spray pyrolysis, has a BET of 246 m 2 / g of fumed magnesium oxide particles.

[0107] MgO 805, which has a BET of 234m 2 / g, use Magnesium oxide particles surface modified with OCTMO (octyltrimethoxysilane).

[0108] Preparation of metal oxide particles:

[0109] Comparative Example 1: Preparation of surface modified aluminum oxide Alu 130 805

[0110] Take 300g as Alumina particles prepared by pyrolysis of Alu 130 were placed in a mixer and mixed with 48 g of octyltrimethoxysilane (C 11 H 26 O 3 After the spraying of silane on the powder was completed, mixing was continued for another 5 minutes. Then, tempering of the wetted powder was carried out in an oven at 130° C. for 3 hours.

[0111] The hydrophilic and surface modified alumina has the particle property data provided in Table 1.

[0112] Comparative Example 2: Alu 200

[0113] First, aluminum chloride (AlCl 3 ), and 0.8kg / h AlCl 3 In addition, 0.7m 3 / h of combustion gas H 2 and 6.6m 3 / h of primary air is introduced into the mixing chamber. The reaction mixture is sent to the burner in the central tube and ignited. The flame burns in the water-cooled reaction chamber. In order to shield the flame, 4.5m 3 / h of secondary air was introduced into the reaction chamber. The powder formed was deposited in a downstream filter and then treated with air and steam in countercurrent at about 660° C. The particle property characteristics of the prepared powder are provided in Table 1.

[0114] Comparative Example 3: Preparation of Magnesium Oxide (MgO-01) Prepared by Pyrolysis

[0115] Prepare 8.0 kg of a solution containing 480 g of magnesium nitrate (Mg(NO 3 ) 2 6H 2 O) in aqueous solution. 2.5 kg / h of this dispersion and 15 Nm 3 / h of air aerosol and sprayed into a tubular reaction with a combustion flame. The combustion gas of the flame is 16Nm 3 / h of hydrogen and 30Nm 3 / h of air composition. In addition, using 25Nm 3 / h of secondary air. After the reactor, the reaction gases were cooled and filtered. The particle property characteristics of the prepared powders are given in Table 1.

[0116] Comparative Example 4: Preparation of pyrolytically prepared magnesium oxide (MgO-08) with high BET surface area

[0117] Prepare 1.89 kg of hydrated magnesium acetate (Mg(CH 3 COO 2 *4H 2 O) in aqueous solution. 2.5 kg / h of this dispersion and 15 Nm 3 / h of air aerosol and sprayed into a tubular reaction with a combustion flame. The combustion gas of the flame is 8Nm 3 / h of hydrogen and 30Nm 3 / h of air composition. In addition, using 25Nm 3 / h of secondary air. After the reactor, the reaction gases are cooled and filtered. The high surface area, pyrolytically prepared hydrophilic magnesium oxide formed has the physical property data shown in Table 1.

[0118] Example 1: Preparation of surface modified magnesium oxide (MgO-805)

[0119] 300 g of the pyrolytically prepared magnesium oxide (Example 4) was placed in a mixer and mixed with 72 g of octyltrimethoxysilane (C 11 H 26 O 3 After the spraying of silane on the powder was completed, mixing was continued for another 5 minutes. Then, tempering of the wetted powder was carried out in an oven at 130° C. for 3 hours.

[0120] The hydrophilic and surface-modified magnesium oxide has the physicochemical property data shown in Table 1.

[0121] Table 1. Physical properties of the tested metal compound particles

[0122]

[0123] Preparation of coated electrode sheets

[0124] Comparative Example 5

[0125] A copper foil having a thickness of 12 μm and covered with a lithium metal layer having a thickness of 100 μm is provided. Alu130 particles were dispersed in 1,2-dimethoxyethane (DME, C 4 H 10 O 2 ) to obtain a first solution with a solid content of 5 wt%. Poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP (supplier: Sigma-Aldrich, weight average molecular weight (Mw) about 400,000 g / mol) was also dissolved in DME to obtain a second solution with a solid content of 5 wt%.

[0126] Molecular weight was measured using the ISO 16014 standard.

[0127] The first solution and the second solution are vigorously stirred for several hours and then mixed together in such a ratio under stirring to produce a mixture of 4:1 (by weight) of aluminum oxide to PVDF-HFP copolymer. The mixture is coated on the lithium metal layer by a solvent casting method. Specifically, the original mixture slurry is stirred by a magnetic stirrer in a 20mL sample bottle, and then the mixture slurry is coated on the metal layer using a brush to form a mixture slurry layer covering the lithium metal layer. After applying the coating, the lithium metal layer with the mixture slurry layer is heated at 70 ° C for 30 minutes on a hot plate to evaporate the solvent and form an electrode sheet comprising a lithium metal layer and a coating. During the initial battery cycle, the electrode sheet forms a protective layer with a thickness of about 10 μm. During the initial battery cycle, due to the chemical reaction between the electrolyte and the electrode material, ASEI is formed on the surface of the secondary battery electrode and acts as a protective layer to prevent further reaction.

[0128] Comparative Example 6

[0129] The same procedure as described in Comparative Example 1 was followed except that Alu 130 805 alumina was used instead of Alu 130.

[0130] Comparative Example 7

[0131] The same procedure as described in Comparative Example 1 was followed except that Alu 200 alumina was used instead of Alu 130. After mixing the first solution and the second solution, the coating slurry is not stable in storage for a long time, however, once the coating slurry is prepared, the coating process is immediately performed.

[0132] Comparative Example 8

[0133] The same procedure as described in Comparative Example 1 was carried out except that magnesium oxide of MgO-01 was used instead of Alu 130.

[0134] Comparative Example 9

[0135] The same procedure as described in Comparative Example 1 was performed except that magnesium oxide of MgO-08 was used instead of Alu 130. After mixing the first solution and the second solution, the mixed solution chemically reacted and the color of the mixed solution turned black. Therefore, no further testing was performed.

[0136] Example 2

[0137] The same procedure as described in Comparative Example 1 was carried out except that magnesium oxide of MgO 805 was used instead of Alu 130. After mixing the first solution and the second solution, a stable dispersion was obtained with this surface-modified magnesium oxide particles.

[0138] Comparative Example 10:

[0139] No protective layer was coated on the Li-Cu foil. Li-Cu was used directly as an electrode. Specifically, we used a 12 μm Cu foil with a 100 μm Li layer on top of the Cu foil.

[0140] Fabrication of Li-Li symmetric batteries in ether-type liquid electrolytes

[0141] A 1 M solution of lithium bis(fluorosulfonyl)imide in 1.2:3 mol / mol=1,2-dimethoxyethane:1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether was used as an electrolyte composition.

[0142] The first coated electrode sheet, a polypropylene-polyethylene-polypropylene (PP / PE / PP) separator ( 2320, supplier: Celgard) and a second (same as the first) electrode sheet were placed in sequence (the metal compound coating of each electrode sheet faced the separator) and sealed in a CR2032 button cell.

[0143] Electrochemical properties (battery cycle test)

[0144] Electrochemical cycling tests were performed on an Arbin BT2000 battery tester at room temperature using CR2032 type button cells. The voltage versus time (cycle) curve during galvanostatic cycling of Li-Li cells is relevant to electrode stability and failure.

[0145] At 1.0 mAh / cm 2 The voltage curves of lithium stripping and plating in Li-Li symmetric cells were measured at a current density of .

[0146] Figure 5 Shown at 1mA / cm 2 At a current density of Cycling of polarization voltage using Alu 130 (Comparative Example 5) as filler in the protective layer on the Li layer.

[0147] Figure 6 Shown at 1mA / cm 2 Cycling of polarization voltage using Alu 130 805 (Comparative Example 6) as a filler in the protective layer on the Li layer at a current density of .

[0148] Figure 7 Shown at 1mA / cm 2Cycling of polarization voltage using Alu 200 (Comparative Example 7) as a filler in the protective layer on the Li layer at a current density of .

[0149] Figure 8 Shown at 1mA / cm 2 Cycling of polarization voltage using MgO-01 (Comparative Example 8) as a filler in the protective layer on the Li layer at a current density of .

[0150] Fig. 9 Shown at 1mA / cm 2 Cycling of polarization voltage using MgO 805 (Example 10) as a filler in the protective layer on the Li layer at a current density of .

[0151] Fig.10 It shows that without a protective layer, the 2 Cycling of polarization voltage at a current density of (Comparative Example 10).

[0152] Fig.11 Shown is an example at 1 mA / cm 2 Polarization voltage after 200 cycles at a current density of .

[0153] Table 2. Figure 6 As shown, at the 200th cycle, the average polarization voltage of button cells without or with a protective layer of metal compound / PVDF-HFP in ether-type electrolyte.

[0154] Examples <![CDATA[Polarization voltage at 1.0 mA / cm² at the 200th cycle]]> 2 > Comparative Example 5 0.045V Comparative Example 6 0.059V Comparative Example 7 0.046V Comparative Example 8 0.062V Example 2 0.021V Comparative Example 10 0.052V

[0155] The coated electrode sheet of Example 2 showed the most stable cycling performance at the lowest polarization voltage. This means that the resistance of the battery using the surface-modified magnesium oxide can provide stable coating dispersion and stable electrochemical performance in a lithium metal battery having a protective layer composition of magnesium oxide particles and PVDF-HFP in a weight ratio of 4:1.

[0156] Although the present invention has been described with reference to specific embodiments, it should be noted that the embodiments provided are not intended to limit the scope of the invention and that many other variations of the described embodiments as well as other embodiments of the invention may be conceived by those skilled in the art after reading this disclosure without departing from the scope of the invention as defined in the appended claims.

[0157] Reference Number List

[0158] ------------------------------------

[0159] 8 metal foil

[0160] 10 Metal Layer

[0161] 11 Electrodes

[0162] 14 Coating

[0163] OB Organic Binder

[0164] MC Metal Compounds

[0165] 102, 104, 106, method steps 400 Electrical or electronic devices

[0166] 40 Batteries

[0167] 16 Diaphragm

[0168] 18 Diaphragm coating

[0169] 20 Active Materials

[0170] 22 Electrode Plate

[0171] 24 Electrolytes

Claims

1. A composition for a coating of an electrode of a lithium battery, the composition comprising an organic binder and a metal compound, the metal compound being selected from hydrophobic surface-modified fumed magnesium oxide, hydrophobic surface-modified fumed lithium-doped magnesium oxide, hydrophobic surface-modified fumed magnesium phosphate or a mixture thereof, wherein the metal compound comprises aggregates of primary particles, wherein the weight ratio of the metal compound to the organic binder in the composition is 0.1 to 10, and wherein the binder is selected from poly(vinylidene fluoride), a copolymer of vinylidene fluoride and hexafluoropropylene, poly(vinyl acetate), poly(ethylene oxide), poly( methyl methacrylate), poly(ethyl acrylate), poly(vinyl chloride), poly(urethane), poly(acrylonitrile), poly(ethylene glycol), polypropylene glycol, poly(ethylene glycol-co-propylene glycol-co-ethylene glycol), poly(propylene glycol-co-ethylene glycol-co-propylene glycol), polysiloxanes, poly(oxyethylene) methacrylate, poly(ethylene glycol) diacrylate, poly(propylene glycol) diacrylate, poly(ethylene glycol) dimethacrylate, poly(propylene glycol) dimethacrylate, poly(ethylene glycol)-dimethyl ether, poly(ether amines), copolymers of ethylene and vinyl acetate, carboxymethyl cellulose, poly(imides), and mixtures thereof.

2. The composition according to claim 1, wherein the weight ratio of the metal compound to the organic binder is from 0.2 to 9.5, more preferably from 0.3 to 9.0, even more preferably from 0.4 to 8.5, even more preferably from 0.5 to 8.0, even more preferably from 0.8 to 7.0 and most preferably from 1.0 to 6.

0.

3. The composition according to any one of the preceding claims, wherein the metal compound has a tamped density of 20 g / L - 1000 g / L, preferably 20 g / L - 200 g / L, more preferably 25 g / L - 150 g / L, even more preferably 28 g / L - 130 g / L and most preferably 30 g / L - 120 g / L, wherein the tamped density is determined according to DIN ISO 787-11: 1995.

4. A composition according to any one of the preceding claims, wherein the surface modified metal compound has a methanol wettability of greater than 5 vol%, preferably from 10 vol% to 80 vol%, more preferably from 15 vol% to 70 vol%, even more preferably from 20 vol% to 65 vol%, most preferably from 25 vol% to 60 vol%, measured as described in the description.

5. The composition according to any one of the preceding claims, further comprising a lithium salt mixed with the binder and the metal compound, the lithium salt being selected from lithium hexafluorophosphate (LiPF6), lithium bis-2-(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), Li2SiF6, lithium trifluoromethanesulfonate, lithium bis(perfluoroethylsulfonyl)imide (LiN(SO2CF2CF3)2), lithium nitrate, lithium bis(oxalate)borate, lithium cyclo-difluoromethane-1,1-bis(sulfonyl)imide , lithium cyclohexafluoropropane-1,1-bis(sulfonyl)imide and mixtures thereof, and / or wherein the metal compound is modified with a surface treatment agent selected from organosilanes, silazanes, acyclic polysiloxanes, cyclic polysiloxanes and mixtures thereof to become hydrophobic, and wherein the hydrophobic metal compound preferably has a carbon content of 0.1 wt% to 15.0 wt%, more preferably 0.5 wt% to 12.0 wt%, even more preferably 1.0 wt% to 10.0 wt% and most preferably 1.5 wt% to 8.0 wt%, wherein the carbon content is determined by elemental analysis according to EN ISO 3262-20:2000 (Chapter 8).

6. An electrode for a lithium battery, the electrode 11 comprising a coating 14 formed on a metal layer 10 of the electrode 11, characterized in that: The coating 14 comprises the composition of any one of the preceding claims.

7. The electrode according to claim 6, wherein the weight ratio of the metal compound MC to the organic binder OB in the coating 14 is 0.1 to 10, preferably 0.2 to 9.5, more preferably 0.3 to 9.0, even more preferably 0.4 to 8.5, even more preferably 0.5 to 8.0, even more preferably 0.8 to 7.0 and most preferably 1.0 to 6.

0.

8. The electrode according to claim 6 or 7, further comprising a lithium salt added to the coating, and / or wherein the coating can have a thickness of 0.1 μm - 300 μm, more preferably 0.5 μm - 100 μm, even more preferably 1 μm - 50 μm, most preferably 2 μm - 20 μm.

9. A method for preparing an electrode (11) according to any one of claims 6 to 8, the method comprising: preparing at least one mixture comprising an organic binder OB and a metal compound MC to prepare a first mixture (102), coating the first mixture on the surface of the metal layer (10) to form a pre-coating layer (104); and drying and / or curing the pre-coating layer (106) to form a coating layer (14), wherein the binder is selected from the group consisting of poly(vinylidene fluoride), a copolymer of vinylidene fluoride and hexafluoropropylene, poly(vinyl acetate), poly(ethylene oxide), poly(methyl methacrylate), poly(ethyl acrylate), poly(vinyl chloride), poly(urethane), poly(acrylonitrile), poly(ethylene glycol), polypropylene glycol, poly(ethylene glycol-co-propylene glycol-co-ethylene glycol), poly(propylene glycol-co-ethylene glycol), and poly(propylene glycol-co-ethylene glycol). -propylene glycol), polysiloxane, poly(oxyethylene) methacrylate, poly(ethylene glycol) diacrylate, poly(propylene glycol) diacrylate, poly(ethylene glycol) dimethacrylate, poly(propylene glycol) dimethacrylate, poly(ethylene glycol)-dimethyl ether, poly(ether amine), copolymers of ethylene and vinyl acetate, carboxymethyl cellulose, poly(imide) and mixtures thereof, the metal compound MC is selected from hydrophobic surface-modified fumed magnesium oxide, hydrophobic surface-modified fumed lithium-doped magnesium oxide, hydrophobic surface-modified fumed magnesium phosphate or mixtures thereof, wherein the metal compound comprises aggregates of primary particles, wherein the weight ratio of the metal compound to the organic binder in the composition is 0.1 to 10.

10. The method according to claim 9, wherein the at least one mixture comprises a first mixture comprising metal compound particles and a first solvent and a second mixture comprising an organic binder, a second solvent and optionally a lithium salt, wherein the first solvent and the second solvent are the same or different, wherein the first mixture comprises preferably 1%-70%, more preferably 3%-60%, even more preferably 5%-50%, and most preferably 7%-45% by weight of the metal compound and 30%-99%, more preferably 40%-97%, even more preferably 50%-95%, and most preferably 55%-93% by weight of the solvent, wherein the second mixture comprises 0.1%-90%, preferably 0.5%-50%, more preferably 1%-20%, more preferably 2%-10% by weight of the organic binder and 10%-99.9%, preferably 50%-99.5%, more preferably 80%-99%, more preferably 90%-98% by weight of the solvent, and wherein curing of the coating mixture comprises a chemical reaction, a physical curing or a combination thereof.

11. The method according to claim 9 or 10, wherein the drying and / or curing step (106) is preferably carried out at a temperature of 0°C to 500°C, more preferably 5°C to 400°C, more preferably 10°C to 300°C, more preferably 20°C to 200°C, in the presence of air, or preferably with the exclusion of oxygen, under a nitrogen or argon protective gas atmosphere and at standard pressure or under reduced pressure, for example under vacuum.

12. The method according to any one of claims 9 to 11, wherein the metal compound is obtained by a pyrolysis process involving flame oxidation, flame hydrolysis and / or flame pyrolysis of starting materials in a hydrogen and / or oxygen flame, wherein the starting material for the metal compound is an organic and / or inorganic metal compound, such as metal chlorides, metal nitrates, metal acetates, metal carboxylates.

13. The method according to any one of the preceding claims, wherein the metal compound is obtained by flame spray pyrolysis, wherein a metal precursor such as a metal chloride is vaporized and reacted in a flame generated by the reaction of hydrogen and oxygen to form a metal compound in particle form, and wherein the metal compound comprises aggregates of primary particles and a BET specific surface area of ​​1 m2 determined by nitrogen adsorption according to the Brunauer-Emmett-Teller method according to DIN 9277:2014. 2 / g to 500m 2 / g, more preferably 20m 2 / g to 400m 2 / g, even more preferably 40m 2 / g to 350m 2 / g and most preferably 50m 2 / g to 300m 2 / g of some primary particles, wherein the number average aggregate particle size d50 is less than 2 μm, preferably 20 nm-1 μm, more preferably 30 nm-800 nm, even more preferably 40 nm-600 nm and most preferably 50 nm-500 nm, wherein the number average particle size d50 is determined by dynamic light scattering (DLS) in aqueous dispersion.

14. The method according to any one of the preceding claims, wherein the metal compound is obtained by pyrolysis followed by ultrasound, thereby destroying agglomerates and partially destroying some aggregates to obtain a powder with smaller particle size and narrower particle size distribution, wherein preferably, the number average aggregate particle size d50 of the metal compound after ultrasound is 50nm-1000nm, more preferably 100nm-700nm, even more preferably 150nm-500nm, as measured at 25°C on a powder consisting of 5% by weight of the particles and 95% by weight of the particles. The metal compound particles preferably have a span (d90-d10) / d50 of 0.4-1.2, more preferably 0.5-1.1, even more preferably 0.6-1.0, as determined by dynamic light scattering (DLS) after ultrasonic treatment for 300 seconds on a mixture consisting of 5 wt. % of the particles and 95 wt. % of a 0.5 g / L sodium pyrophosphate aqueous solution at 25°C.

15. A lithium battery comprising the electrode 11 according to any one of claims 6 to 8.

16. A device comprising the lithium battery of claim 15, the device comprising an electrical or electronic device, including a mobile phone, an electronic watch, a camera, a remote control key, a laptop computer, a desktop computer, a tablet computer, a power tool, a vacuum cleaner, an electric lawn mower, a robot, an electrical appliance, an electric aircraft, and an electric vehicle.

Citation Information

Patent Citations

  • Composite metal lithium negative electrode and preparation method thereof

    CN109473627A

  • Composite protective layer for lithium metal anode and method of making the same

    US20140220439A1

  • Lithium metal battery

    US20170062829A1

  • Polymer protecting layer, lithium metal negative electrode, lithium secondary battery

    US20170301920A1

  • Negative electrode for lithium metal battery, method of preparing negative electrode, and lithium metal battery including the same

    US20180316051A1